2021
DOI: 10.1177/2040622320987057
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals rotator cuff injury caused by oxidative stress

Abstract: Background and aims: Rotator cuff tendinopathy is common and is related to pain and dysfunction. However, the pathological mechanism of rotator cuff injury and shoulder pain is unclear. Objective: to investigate the pathological mechanism of rotator cuff injury and shoulder pain, and screen out the marker proteins related to rotator cuff injury by proteomics. Methods: Subacromial synovium specimens were collected from patients undergoing shoulder arthroscopic surgery. The experimental group were patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Associations between the bursa proteome and the underlying injured tendon suggested that there was cross-talk between these two tissues, although this requires further study. These findings are consistent with a study showing up-regulated markers of oxidative stress and chronic inflammation in bursa tissue from patients with rotator cuff tears compared with those with shoulder instability, indicating that the bursa proteome was dependent on the pathological state of the rotator cuff ( 29 ). The cellular makeup of healthy human bursa tissue is difficult to study because access to healthy bursa tissue samples is limited.…”
Section: Discussionsupporting
confidence: 92%
“…Associations between the bursa proteome and the underlying injured tendon suggested that there was cross-talk between these two tissues, although this requires further study. These findings are consistent with a study showing up-regulated markers of oxidative stress and chronic inflammation in bursa tissue from patients with rotator cuff tears compared with those with shoulder instability, indicating that the bursa proteome was dependent on the pathological state of the rotator cuff ( 29 ). The cellular makeup of healthy human bursa tissue is difficult to study because access to healthy bursa tissue samples is limited.…”
Section: Discussionsupporting
confidence: 92%
“…TMAO-upregulated PLIN4 , also upregulated in brain by fasting, plays a key role in intracellular trafficking of lipids ( 97 ), lipid droplet formation, and adipocyte differentiation ( 98 ). PLIN4 was upregulated in rotator cuff injury synovium and was functionally related to oxidative stress and chronic inflammation ( 99 ). OGDHL was upregulated by a phosphorylation-dependent transcription factor CREB ( 100 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has applied proteomic approach in uncovering the protein level changes along with RCT ( Sejersen et al, 2015 ; Yuan et al, 2021 ). Matrix metalloproteinases (MMPs) were found to be involved in the pathogenesis of RCT, and a remodeling of extracellular matrix (ECM) was reflected by the alteration of MMPs and collagen expression.…”
Section: Introductionmentioning
confidence: 99%